EVALUASI SISTEM PENGENDALIAN INTERNAL TERHADAP SIKLUS PENDAPATAN PADA PT INDRA KARYA (PERSERO) WILAYAH I MALANG - Sari, Fransisca Diah Permata (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The purpose of the research is to get knowledge about the the compliance of the implementation of the internal control system at PT Indra Karya (Persero) Region I Malang, which is based on Mulyadi 2008 standard that reveals on supplementary factors and inhibiting factors, and this research also inform us about the recommendation for the implementation of internal control system at PT Indra Karya (Persero) Region I Malang. The internalÂ implementation system of revenue cycle at PT Indra Karya (Persero) Region I Malang, uses analysis of the elements of internal control, environment control system of internal control, accounting internal control which is on electronic data management base on Mulyadi 2008.Â Based on this analysis, the overall system internal control is still not good in the application in the field. Implementation of internal control that complies with the standards Mulyadi, 2008, the appropriateness of the control environment, general controls over the accounting internal control, and application control on accounting internal control. A mismatch occurs in the element of internal control, that are: 1) the lack of good separation of the operating functions work in accounting sub-sections, 2) the implementation and unknown of the employees about operational system the company especially of the revenue cycle, 3) indiscipline in executing authority system of authorization, 4) there is no suddenly inspections, 5) human resources are still many inadequate, 6) lack of effective management policies in exercising their several production projects, 7) and there is no accounting management policies for allowance for doubtful accounts. Â Keywords: Evaluation, Internal Control Systems, Revenue Cycle, PT Indra Karya (Persero) Region I Malang.